2021
DOI: 10.3390/dj9040038
|View full text |Cite
|
Sign up to set email alerts
|

Survival Rate of Zygomatic Implants for Fixed Oral Maxillary Rehabilitations: A Systematic Review and Meta-Analysis Comparing Outcomes between Zygomatic and Regular Implants

Abstract: Background: Zygomatic implants have been proposed alone or in combination with premaxillary conventional implants for severe resorbed maxillary atrophy rehabilitation. The aim of the present investigation was to evaluate through a qualitative systematic review and meta-analysis the survival rate of zygomatic implants in conjunction with regular fixtures for maxillary rehabilitation. Methods: The article screening was conducted on the PubMed/Medline and EMBASE electronic databases according to the “Preferred Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 62 publications
0
9
0
2
Order By: Relevance
“…There was also no significant difference ( P = 0.44) by the EZI technique (retrospective studies). A previous SR 60 observed that ZI had a significantly higher survival rate ( P = 0.02) compared with CI. However, this review includes studies with shorter follow‐up times, which may have influenced the results.…”
Section: Discussionmentioning
confidence: 82%
“…There was also no significant difference ( P = 0.44) by the EZI technique (retrospective studies). A previous SR 60 observed that ZI had a significantly higher survival rate ( P = 0.02) compared with CI. However, this review includes studies with shorter follow‐up times, which may have influenced the results.…”
Section: Discussionmentioning
confidence: 82%
“…The effectiveness of the present study showed an excellent primary stability of the test implants in the area of the atrophic distal maxilla, while the results speak in favour of the use of very well mineralized bone, such as palatal bone and pterygoid plates of the sphenoid bone, used in anchoring tubero-pterygoid implants [33,[44][45][46][47][48][49][50].…”
Section: Discussionmentioning
confidence: 88%
“…In the second instance, the present study aimed to evaluate the reliability of the surgical procedure performed on an artificial bone substrate measuring the primary stability and the micromovement response with an intra-operator agreement approach. As reported by the mechanostatic theory by Frost [28], this evidence is recurrent in the edentulous jaws area with an overloading generated by a passive prosthetic function that is able to generate severe bone resorption that could invalidate an efficient implant-supported rehabilitation in maxillary atrophic areas [29][30][31][32][33]. In this way, the different experimental conditions considered a wide density pool in order to evaluate the behaviour and the mechanical response of the tested implants in a very critical clinical occurrence, while the most frequent intra-operative complication in this region during the implant positioning is the early loss of fixture stability [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, osteoinductive biomaterials should be able to recruit progenitor cells (MCS) to the grafted site, induce the formation of osteoblasts by differentiating progenitor cells (MCS) in mature cells and eventually regenerate ectopic bone where there is no extraskeletal structure [ 36 ]. The prevalence of implant failure and wear has been related to the presence of inflammation and infections as a result of oral diseases, such as peri-implant and oral flora disorders/dysbiosis [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. The biophysical and biochemical properties of biomaterials could influence the cellular responses, including the macro-topography, pore geometry and stiffness, surface chemistry, rate of degradation and presence of biomolecules, influence proliferation and differentiation to eventually give tissue regeneration [ 48 , 49 ].…”
Section: Introductionmentioning
confidence: 99%